Remeasuring Scale in Active Management - Huang, Shiyang; Lu, Xu; Song, Yang; Xiang, Hong (Review of Financial Studies, 2026)
We show that scale in active equity portfolios is understated by at least 65% because the majority of mutual funds have “twin” institutional vehicles (IVs) managed under the same strategies. Omitting these IVs can severely skew crucial estimates in asset management research: by including IV assets, diminishing returns to scale of active investments is significantly reduced, and dollar value added of active strategies is more substantial and persistent than previously suggested. We further show that IV assets meaningfully influence managers’ portfolio decisions. In addition, these measurement issues apply to common flow measures and extend to passive funds and bond funds.